Teacher's Strategy in Managing Classes in Online Economics Learning to Increase Motivation and Achievement in Economics Learning for Class XI Social Sciences - Rinto Alexandro (JTP - Jurnal Teknologi Pendidikan, 2021)
has affected all sectors, especially the education sector. Due to the Covid-19 pandemic, the implementation of learning in schools which was initially carried out face-to-face must be abolished and replaced with online learning (in the network). The purpose of this study is to determine the effect of online learning on students' motivation and economic learning achievement. Researchers obtained data from questionnaires distributed to 47 students of SMA class XI IPS at SMA Negeri 1 Palangka Raya as online respondents. Research subjects were selected by random sampling method. Questionnaires were used to determine the effect of online learning on motivation and economic achievement in class XI students. Based on the results of the study, online learning does not provide too significant obstacles for students in understanding the subject matter and does not make students' learning achievement in economics decrease. In some students, the motivation to study economics decreases because they cannot understand the subject matter delivered by the teacher which is not optimal and does not vary so that it has an impact on student learning achievement. Students want online learning that is interesting, fun, varied, and creative. motivation to learn economics decreases because they cannot understand the subject matter delivered by the teacher which is not optimal and does not vary so that it has an impact on student learning achievement. Students want online learning that is interesting, fun, varied, and creative. motivation to learn economics decreases because they cannot understand the subject matter delivered by the teacher which is not optimal and does not vary so that it has an impact on student learning achievement. Students want online learning that is interesting, fun, varied, and creative.